Desain Kontrol Sistem Eksitasi Steam Turbine Generator (Stg) Pada Combine Cycle Power Plant 120 Mw Pt.Krakatau Daya Istrik Menggunakan Jaringan Syaraf Tiruan Backpropagation - Muhamad Otong; Ri Munarto; Dasep Iskandar (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
Excitation System is a vital part of generating electricity in the generator, the function of the excitation system in the generator is to control the output of the generator to remain stable at the changing system load. The excitation control system of the synchronous generator is one of the steps to improve the stability of the power system and to ensure the quality of the electricity generated by the network. In this research used one of the implementation of artificial intelligence technology is Artificial Neural Network designed as controller excitation system generator. The network is designed using a backpropagation learning algorithm, and the Lavenberg-Marquardt training algorithm with a  feedforward multilayer network architecture. The result of simulated test and training using Matlab application obtained with presentation of system success equal to 96,387%.